Breakdown of simple female genital fistula repair after 7 day versus 14 day postoperative bladder catheterisation: a randomised, controlled, open-label, non-inferiority trial. Issue 9988 (4th July 2015) - Barone, Mark A; Widmer, Mariana; Arrowsmith, Steven; Ruminjo, Joseph; Seuc, Armando; Landry, Evelyn; Barry, Thierno Hamidou; Danladi, Dantani; Djangnikpo, Lucien; Gbawuru-Mansaray, Tagie; Harou, Issoufa; Lewis, Alyona; et al.
Summary: Background: Duration of bladder catheterisation after female genital fistula repair varies widely. We aimed to establish whether 7 day bladder catheterisation was non-inferior to 14 days in terms of incidence of fistula repair breakdown in women with simple fistula. Methods: In this randomised, controlled, open-label, non-inferiority trial, we enrolled patients at eight hospitals in the Democratic Republic of the Congo, Ethiopia, Guinea, Kenya, Niger, Nigeria, Sierra Leone, and Uganda. Consenting patients were eligible if they had a simple fistula that was closed after surgery and remained closed 7 days after surgery, understood study procedures and requirements, and agreed to return for follow-up 3 months after surgery. We excluded women if their fistula was not simple or was radiation-induced, associated with cancer, or due to lymphogranuloma venereum; if they were pregnant; or if they had multiple fistula. A research assistant at each site randomly allocated participants 1:1 (randomly varying block sizes of 4–6; stratified by country) to 7 day or 14 day bladder catheterisation (via a random allocation sequence computer generated centrally by WHO). Outcome assessors were not masked to treatment assignment. The primary outcome was fistula repair breakdown, on the basis of dye test results, any time between 8 days after catheter removal and 3 months after surgery. The non-inferiority margin was 10%, assessed in the per-protocol population. This trial is registered with ClinicalTrials.gov, number NCT01428830 . Findings: We randomly allocated 524 participants between March 7, 2012, and May 6, 2013; 261 in the 7 day group and 263 in the 14 day group. In the per-protocol analysis, ten (4%) of 250 patients had repair breakdown in the 7 day group (95% CI 2–8) compared with eight (3%) of 251 (2–6) in the 14 day group (risk difference 0·8% [95% CI −2·8 to 4·5]), meeting the criteria for non-inferiority. Interpretation: 7 day bladder catheterisation after repair of simple fistula is non-inferior to 14 day catheterisation and could be used for management of women after repair of simple fistula with no evidence of a significantly increased risk of repair breakdown, urinary retention, or residual incontinence up to 3 months after surgery. Funding: US Agency for International Development.